"Auditoria de gestión y su incidencia en los servicios académicos del colegio de bachillerato técnico "Rafael Vásconez Gómez" del cantón La Mana, año 2014 - Laje Laje, Lady Laura (2016)
Currently, the Performance Audit becomes an important element management, facilitates the use of methods that objectively show the level of management and organizational situation. This helps managers to solve economic, social and ecological problems within the organization, to create a healthy dynamic that will lead to the success of the goals. The methods and techniques used are primarily general, predestined to detect weaknesses in the company, the following study was developed by applying the hypothetical-deductive, analytical, inductive method, also investigative techniques as they are the observation of internal control questionnaire by applying the COSO I to determine the level of academic services of the institution to make research more efficient and thus detect deficiencies in that area and to the respective recommendations for the proper functioning thereof, so as to analyze and seek improvement actions. Every aspect of the company, including corporate goals is evaluated, the organizational structure, the performance of each employee, compliance with the regulations of the institution, efficiency and economy, the accuracy of the information is verified. Also it wants to contribute to academic progress, contributing to knowledge and provides support for future research of economic order of another aspect. Thus you want to contribute practical solutions through an audit that promote quality improvement in the academic services of the College of Technical High School "Rafael Gomez Vásconez". It is recommended. It is recommended to carry out the activities in accordance with the provisions of the internal rules of the institution for the efficient performance of its functions and develop ongoing training programs for teachers; implement a mechanism which allows access to academic software according the degree of authority, protection of academic information; conduct a periodic review of the strategic plan of the College in order to verify compliance with all the activities and make sure that you take into account all the recommendations outlined in the audit report